The Effect of Flipped Classroom Learning Assisted by Computer Simulation on Students' Comprehension of Simple Harmonic Motion - Theo Jhoni Hartanto; Suhartono; Budi Santoso; Zen Frianto (Postgraduate, University of Mataram, 2024)
Innovation in science learning is highly recommended by various studies and education experts. Through this learning innovation, teachers create learning that facilitates students' curiosity by getting them involved in learning, which ultimately helps them understand science in depth. However, the current trend is that science classes